STUDI ZINK OKSIDA SEBAGAI KOMPOSIT BIOPLASTIK GENUS METROXXLEN, Sp DENGAN METODE MELT INTERCALTION - Khairun Nisah (UIN AR-RANIRY, 2019)
Bioplastic is one step to reduce the use of plastics that are not environmentally friendly. The genus Metroxxlen, Sp is a bioplastic material that is easily degraded in the soil. Metroxxlen, Sp has a hydrophilic nature which results in its physical properties being low. Bioplastic Starch Genus Metroxxlen, Sp is made by mixing ZnO as a reinforcement, Genus starch Metroxxlen, Sp as a source of natural polymers, with the addition of glycerol as a plasticizer. The results of the spread of ZnO in bioplastics can be seen with SEM. Comparison of ZnO with Genus Metroxxlen Sp. starch 1-3% wt produced a strengthened mechanism characteristic from 0.40 kg/cm2 to 0.70 kgf /cm2; the change in the extension changed down from 120.4% to 99.00%. For glycerol composition with variations from 1-3% wt, the change in elongation changes to increase from 90.00% to 98.00%, the nature of the mechanism changes to decrease from 0.25 kg/cm2 to 0.20 kgf /cm2.